If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(8 + 5x) = -84 (8 * -3 + 5x * -3) = -84 (-24 + -15x) = -84 Solving -24 + -15x = -84 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -15x = -84 + 24 Combine like terms: -24 + 24 = 0 0 + -15x = -84 + 24 -15x = -84 + 24 Combine like terms: -84 + 24 = -60 -15x = -60 Divide each side by '-15'. x = 4 Simplifying x = 4
| 6x=10x-32 | | 2x^2+7x-22=0 | | 5-6(7a-5)=287 | | 12k^2-8k= | | -5(7p+2)=4p+9 | | 2x+45=7x+5 | | -6-8m=10-2m-8m | | 4+t=-16 | | (3*4)*7=3*(4*7) | | 0=-16t^2+13t+16 | | 4e^8t=6e^7t | | p+6=10 | | 3-4t=-3(t-1) | | 6x-32=3y-8 | | 6(4+3x)=132 | | 8x=10x-30 | | 2(x+5)-2=1.5(10-x) | | 7(m-n)-3(p+2m)=37 | | 9x-14x=4 | | -8+w=1 | | 14-9+2= | | 107=p-(-130) | | 3x^2-7x+15x=8 | | z-9=3 | | 2p+4(p+6)=3(1-5p) | | -[7x-(2x+1)]=-5-[3(3x-3)-2x] | | 16x-6=13x+9 | | 5(5x-16)=25x-80 | | 0.25m+25=0.50m+15 | | 2(8y-4)= | | x=5+-1.33y | | dx+b=3(x-d) |